BACKGROUND RADIATION MEASUREMENTS AND CANCER RISK ESTIMATES FOR ŞEBINKARAHISAR, TURKEY - Kurnaz, Asli (Oxford University Press (OUP), 2013)
Abstract This paper presents the measurement results of environmental radioactivity levels for Şebinkarahisar district (uranium–thorium area), Giresun, Turkey. The radioactivity concentrations of 238 U, 232 Th, 40 K and the fission product 137 Cs in soil samples collected from 73 regions from the surroundings of the study area were determined. In situ measurements of the gamma dose rate in air were performed in the same 73 locations where the soil samples were collected using a portable NaI detector. Also the mean radioactivity concentrations of 238 U, 232 Th and 40 K in rock samples collected from 50 regions were determined. The mean estimated cancer risk value was found. The seasonal variations of the indoor radon activity concentrations were determined in the 30 dwellings in the study area. In addition, the mean gross alpha, gross beta and radon activities in tap water samples were determined in the same 30 dwellings. The excess lifetime cancer risk was calculated using the risk factors of International Commission on Radiological Protection and Biological Effects of Ionizing Radiation. Radiological maps of the Şebinkarahisar region were composed using the results obtained from this study.
Keywords: 13. Climate action; 6. Clean water